Envisioning a Promising Africa From Diverse Perspectives - Cheryl Potgieter; Vimbai Chibango; Imraan Buccus; Takalani G. Tshitangano; Lebohang N. Ndaba; Kunle M. Oparinde; Duduzile Mzindle; Kgomotlokoa L. Thaba-Nkadimene; Ngozi E. Iyoho; Emeka J. Onyetube; Lifutso Tsephe; Khethiwe Dongwe; et al. (AOSIS, 2025)
This scholarly book delves into Africa's critical developmental challenges in striving to achieve the United Nations'Sustainable Development Goals (SDGs) and the African Union's Agenda 2063: The Africa We Want. Adopting a multidisciplinary approach, the book disseminates novel inquiry on interconnected themes spanning gender equity, social transformation and health development. Aligned with Agenda 2063's seven aspirations, the book highlights Africa's shared goals for prosperity, unity, free citizenship and empowerment, particularly for women and youth. Chapters critically examine barriers to achieving these aspirations, offering local, regional and global perspectives on systemic challenges. The first theme, ‘Social cohesion and transformation', examines issues like institutional reform in Nigeria's education sector and the marginalisation of African migrants. The second theme, ‘Gender injustice in education and science', explores topics such as gender gaps in doctoral programmes, resilience among black academics, and cultural stereotyping in teacher education. The final theme, ‘Health and development', focuses on resilience, nutrition and the gendered impacts of the coronavirus disease 2019 (COVID-19). With contributions from leading African scholars, this book critically analyses systemic obstacles and proposes pathways for meaningful progress. Envisioning a promising Africa from diverse perspectives is essential for academics and researchers and is a call to action to confront the barriers impeding Africa's sustainable development goals.